From Compulsion to Character: Parental Digital Discipleship through Sabbath Rhythms in a Smart Society - Soegiarto, Samuel (Aletheia Christian Educators Journal, 2026)
This study explores how parents can disciple elementary-aged children to navigate the addictive mechanisms of digital gaming. It provides a theological framework transforming digital play from a "compulsion loop" into a space for character formation. Utilizing Richard Osmer’s framework, this research conducts a four-fold task: descriptive-empirical (analyzing "pleasurable bondage"), interpretive (dissecting dysfunctional liturgies), normative (constructing Sabbath and Imago Dei theology), and pragmatic (outlining parental discipleship strategies). Compulsion loops exploit the "restless heart" through a "counterfeit grace". However, Sabbath rhythms foster essential virtues like self-control, presence, and gratitude. The Sabbath provides a telos reorienting desires toward God’s finished work. This paper fills a gap in Christian elementary education by integrating behavioral psychology with Reformed theology. It offers a "third way" of discerning engagement for families in a smart society. Practical/Social Implications. The study proposes "counter-praxis" for the home: "Gaming Sabbath" rhythms, "closing liturgies," and dialogical reflection tools for parents to evaluate digital play's spiritual impact. This study is primarily theoretical. Future research should include empirical studies on the long-term impact of Sabbath practices on character development in elementary students.